1996
DOI: 10.1007/bf02230364
|View full text |Cite
|
Sign up to set email alerts
|

Linear scleroderma and melorheostosis: Case presentation and literature review

Abstract: The case of a 9 year-old male patient with linear scleroderma and melorheostosis of the iliac bone is described. Radiological findings suggestive of osteopoikilosis were found in carpal and tarsal bones. A review of the literature on this unusual disease association is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Soft tissue abnormalities overlying MEL (59) can also include skin changes; (17) scleroderma-like patches over MEL have been documented since 1936. (511) Furthermore, linear scleroderma with MEL in OPK/BOS and resembling OPK has been described. (25–27) In 2003, Tinschert et al (34) reported an occurrence of extensive sebaceous nevus (LEN of the scalp) accompanying MEL and hypothesized non-allelic didymosis (i.e., twin spotting) as the genetic basis.…”
Section: V) Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissue abnormalities overlying MEL (59) can also include skin changes; (17) scleroderma-like patches over MEL have been documented since 1936. (511) Furthermore, linear scleroderma with MEL in OPK/BOS and resembling OPK has been described. (25–27) In 2003, Tinschert et al (34) reported an occurrence of extensive sebaceous nevus (LEN of the scalp) accompanying MEL and hypothesized non-allelic didymosis (i.e., twin spotting) as the genetic basis.…”
Section: V) Discussionmentioning
confidence: 99%
“…(2–4) Not infrequently, scleroderma-like skin change (SLS), (511) nevi of various types, (12) or vascular abnormalities (13) overlie MEL bone. Sometimes MEL becomes malignant.…”
Section: Ii) Introductionmentioning
confidence: 99%
“…Although a benign dysplasia, the osseous changes can cause morbidity. Skin and subcutaneous tissue involvement can result in fibrosis and joint contractures leading to deformity and limb-length discrepancy (3,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases the soft tissues overlying the bones may show sclerosis [92,93]. The cutaneous manifestations may include scleroderma-like asymmetrical bands of sclerosis, and fibrotic contractures.…”
Section: Other Hereditary Scleroderma-like Dis-ordersmentioning
confidence: 96%